One piece. Collection no. 09 [videorecording (DVD)] - Clinkenbeard, Colleen; Christian, Luci; Oda, Eiichirō, 1975-
When Luffy and his mates drop anchor at the bizarre island of Long Ring Long Land, they're challenged to a Davy Back Fight by the fast-talking Foxy Pirates. The Straw Hats are no strangers to squabbles, but the sacred code of pirates decrees that this contest could cost Luffy his crew! Next on the horizon for the Hats, it's a case of missing memories as everyone but Robin forgets they ever knew each other. Usopp is quick to claim the title of captain, and Zoro does the unthinkable by attacking Luffy! Can Robin recover the crew's lost recollections before disaster strikes? She'd better work fast because far greater foes lie ahead, and the Straw Hats will need all hands on deck if they hope to survive the return of Captain Foxy--and the icy arrival of Admiral Aokiji.